Evaluation and Improvement of Narrative Visualizations - Lezcano Airaldi, Andrea (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2022.20986, 2022)
In the field of Information Visualization, storytelling techniques help to communicate facts and enhance comprehension. The use of data storytelling best practices can inform the process of creating narrative visualizations and increase the quality of charts used in software applications by improving aspects such as memorability or engagement, for instance, supporting end users in the decision-making process. The main goal of this doctoral research is to develop a method for assessing and improving the quality of narrative visualizations in software products, like scatter plots, line, bar, or pie charts, among others. This has included a case study and a systematic mapping study.